Danseigo and joseigo in the film Isshuukan Furenzu - Tasman, Annisa Qamara; Haristiani, Nuria (Universitas Dian Nuswantoro, 2023)
This research is motivated by the characteristics of the Japanese language which are owned by languages from other countries, namely variations in the gender differences of the speakers. Variations in the gender differences of speakers in Japanese are divided into two, namely danseigo (male language variety) and joseigo (female language variety). The purpose of this language variation research is to find out what kinds of languages are used by men and women in a data source, namely the Isshuukan Furenzu film. The method used is descriptive method with a qualitative approach. Data collection was carried out using note-taking techniques. The results of this study found linguistic aspects of the variety of languages based on gender, namely ninshou daimeishi, shuujoshi, and kandoushi. The ninshou daimeishi found were watashi, watashitachi, ore, oretachi, anata, omae, anta, aisu, aitsura, and kanojo. Shuujosi found include zo, ze, sa, wa, wayone, no, noyo, deshou, kashira, yo, and no. Kandoushi found in the form of maa and hora.